Mithila Painting: An Enquiry into Its Historiography and Identity - Regmi, Bhim Nath (Bon Voyage, 2025)
This paper examines how Mithila women produce contemporary arts for ceremonial occasions to reflect cultural and political history. Its archaic customs consistently highlight Hindu Sanskrit culture. The domination of Brahmin and Kayastha women from higher castes has been the central theme of Mithila painting. This tradition has been subverted, and Sahlesh (Harijan painting) has been established as a new hero. The Mithila tradition, which gained international recognition following its exposure to the Western world in the 1930s, has had a profound impact on scholarly discourse and academic inquiry. However, most historians focus on the authenticity and significance of artistic work, which has caused them to ignore the intricacies involved in painting. Mithila paintings have five distinct styles: Bharni, Tantrik, Kachni, Kohbar, and Godna. Bharni. Since there are several ways to interpret the art, a qualitative research approach is employed in this study, and it explores and analyzes the historiographical dynamics of Mithila paintings, and also attempts to demonstrate how the structure of Maithili paintings continues to stress the dominance of central tendencies within the pictorial field, even despite these changes in the painting’s formal qualities. Contemporary Mithila paintings engage deeply with historical consciousness and present-day socio-cultural realities and offer both a reflection and critique of society while challenging traditional hierarchies through emerging voices like Harijan artists.